Рецензія на монографію із синтаксису - Kulbabska, Olena (БДМУ, 2021)
The monograph is devoted to the study of expressive syntax elements. Much attention is given to segmented constructions with nominative of theme and nominative of concept in poetic and journalese texts. These texts are most influenced by colloquial speech and therefore are the focus of syntactic innovation. At the same time, expressive syntactic constructions do not have a single interpretation in linguistics; individual definitions are characterized by synonymous usage. Therefore, it is important to describe the whole complex of syntactic structures that determine the character of written poetic and journalese speech.
Keywords: expressive syntax, segmented constructions, newspaper publicism, nominative of theme, journalistic nominative, informative topic, theme-rheme.